Genre and pleasure : the case of Malay(sian) romantic comedy / Norman Yusoff - Yusoff, Norman (Fakulti Seni Persembahan & UPENA, 2004)
Genres are often regarded as "tools for predicting and regulating the reception of text."' Genres help audiences to become orientated, to navigate their way via the world of the film by reference to familiar features. The resurgence of romantic comedy in contemporary Malaysian cinema can be seen in the context of the pleasure that a genre film offers. By focusing upon the formal, structural and ideological characteristics of Malay(sian) romantic comedy, this essay attempts to explore what is at stake in the relations between genre and spectator pleasures